De l'« École Giffard » à l'Institut français de Grèce (1907-2022) - Manitakis, Nicolas (Mondes méditerranéens et balkaniques (MMB), 2023)
École Giffard, Institut supérieur d'études françaises, Institut français d'Athènes or Institut français de Grèce... the establishment founded in 1907 by the French School at Athens has had many names and undergone many changes, but it has never failed to fulfil its fundamental mission: not only to work on promoting the spread of the French language in Greece, but also, and above all, to encourage a continuous cultural dialogue between the two countries. Ever since it was set up at the start of the 20th century, its own transformations have run alongside those of Greek society, thanks to the determined action of all those involved. It was once frequented by tens of thousands of students and managed a vast network of subsidiary schools, today, it is an essential player in Greek cultural life: so many writers, painters, sculptors, musicians and film directors, as well as scientific researchers from every discipline have walked and continue to walk its halls. This book, based on a huge range of never-before-seen sources and archival documents, retraces the main phases of this shared history.